Formulation Optimisation of Erythrina variegata Wound-Healing Cream - NUR DANIA AIYANI DZUL AZMAN; ALIFF HISYAM A RAZAK (Progress in Engineering Application and Technology, 2026)
This study focuses on the design and optimisation of the cosmetic cream formulated with bioactive extracts from Erythrina variegata for usage in wound-healing application, which utilised a two-step Design of Experiment (DOE) methodology via Design-Expert. In the first phase (DOE-1) the base cream was refined for maximum stability, identifying a formulation of 10 wt% virgin olive oil, 90 wt % of deionised water, and 2.75 phc of Aquagel35 as the most stable foundation. The second phase (DOE-2) focused on the successful integration of Erythrina variegata extract into the base cream at an optimal concentration of 0.5 phc. An optimised mixing speed of 5000 rpm for a duration of 2 minutes was employed to ensure uniform and stable distribution. Comprehensive physicochemical analyses, including accelerated stability test, viscosity determination, and droplet size measurements, confirmed that the optimised cream maintained sufficient consistency. Numerical optimisation performed via Design-Expert confirmed that the formulations selected for both phases demonstrated the highest structural integrity among the experimental sets. Rather than formulating an entirely new mixture based on the theoretical numerical solution, the specific runs from the DOE matrix that most closely aligned with the optimised parameters and highest desirability scores were identified for assessment. These findings demonstrate that the systematic DOE approach effectively produces a stable, high-quality topical formulation suitable for further medicinal application.